Application of a detailed biomass pyrolysis kinetic scheme to hardwood and softwood torrefaction. (1st March 2016) - Anca-Couce, Andrés; Obernberger, Ingwald
Abstract: A detailed pyrolysis kinetic scheme is applied in this work for biomass torrefaction, with a focus on hardwood and softwood. The scheme includes secondary charring reactions, relevant for particles of a certain thickness, and sugar formation is avoided due to the catalytic effect of alkali metals in biomass. The release of acetic acid from hardwood and softwood hemicellulose is also considered. Representative initial compositions of hardwood and softwood are proposed in order to correctly predict mass loss in pyrolysis and torrefaction micro-TGA experiments. The predictions for product composition are validated with torrefaction batch experiments conducted in a lab-scale reactor with beech and spruce. The scheme predicts with good accuracy the yields of permanent gases and the main groups in which the condensable species are classified. The amount of secondary charring reactions is higher in the lab-scale than in the micro-TGA experiments, due to the higher particle size. The main discrepancies can be explained by the limitations of the scheme: reactive drying is not included and xylan is considered as representative for hemicellulose, which leads to deviations in the predictions of some products from softwood, e.g. furans. A more precise description of hemicellulose from softwood would include a hemicellulose reaction scheme based on glucomannan.